2019
DOI: 10.1038/s41386-019-0423-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of RGS12 in the differential regulation of kappa opioid receptor-dependent signaling and behavior

Abstract: Kappa opioid receptor (KOR) agonists show promise in ameliorating disorders, such as addiction and chronic pain, but are limited by dysphoric and aversive side effects. Clinically beneficial effects of KOR agonists (e.g., analgesia) are predominantly mediated by heterotrimeric G protein signaling, whereas β-arrestin signaling is considered central to their detrimental side effects (e.g., dysphoria/aversion). Here we show that Regulator of G protein Signaling-12 (RGS12), via independent signaling mechanisms, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 98 publications
(158 reference statements)
0
15
0
Order By: Relevance
“…Effects of RU-1205: Initiation of the Intravenous Self-administration Reaction in Mice. analgesic effect without causing dysphoria (Ehrich et al 2015;Gross et al 2019), which either have a multi-targeted effect with the properties of selective kappa agonists and p38 MAPK kinase inhibitors, or are "functionally selective" kappa receptor ligands. The term "functional selectivity" or "biased agonism" describes the ability of a ligand of a G-protein-coupled receptor to selectively activate a subset of signaling cascades in a particular GPCR, as opposed to activating all downstream signaling cascades (eg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effects of RU-1205: Initiation of the Intravenous Self-administration Reaction in Mice. analgesic effect without causing dysphoria (Ehrich et al 2015;Gross et al 2019), which either have a multi-targeted effect with the properties of selective kappa agonists and p38 MAPK kinase inhibitors, or are "functionally selective" kappa receptor ligands. The term "functional selectivity" or "biased agonism" describes the ability of a ligand of a G-protein-coupled receptor to selectively activate a subset of signaling cascades in a particular GPCR, as opposed to activating all downstream signaling cascades (eg.…”
Section: Discussionmentioning
confidence: 99%
“…G-proteins, arrestin and/or kinase) (Bruchas et al 2007). It has been suggested that p38 MAPK activation is mediated by β-arrestin-2 signaling, which allows us to consider the therapeutic potential of KOR ligands functionally selective towards G protein and away from β-arrestin2 pathways as analgetics without dysphoric side effects (Gross et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In PC12 cells stably expressing KOR, agonist application increased RGS4 mRNA expression in a KOR antagonist reversible manner, a process that may contribute to desensitization of KOR agonist responses (Nakagawa et al, 2001). Downstream of KOR, RGS12 attenuates G-protein signaling and promotes β-arrestin (Gross et al, 2019). Since β-arrestin is thought to promote unwanted effects of KOR agonists, including aversion, an inhibitor of RGS12 would be expected to promote G-protein signaling and therefore analgesia without dysphoria, as indicated in Figure 1.…”
Section: The Kappa Opioid Receptormentioning
confidence: 99%
“…RGS12, a member of the RGS protein superfamily (Snow et al, 1997; Snow et al, 1998), is abundantly expressed in the embryonic nervous system (Martin-McCaffrey et al, 2005), and it displays appreciable protein expression within some serotonergic projection regions of the adult mouse brain (e.g. cortex, hippocampus, striatum, midbrain) (Gross et al, 2018; Gross et al, 2019). We have previously shown that stimulation of hyperlocomotion by acute administration of DAT-targeting psychostimulants (AMPH, cocaine) is reduced in RGS12-null mice (Gross et al, 2018).…”
Section: Introductionmentioning
confidence: 99%